Effects of servicescape on tourist experience, emotion, perceived value and satisfaction on behavioural intention to visit ecotourism parks in Malaysia - Chok, Nyen Vui (2018)
Tourism is a significant industry within most parts of the worldwide. This industry provides economic contributions that impact on other industries like hotel and accommodation, transportation, entertainment and attractions, and other forms of commercial. Malaysia is one of the many countries that reap the economic benefits from this sector. The tourism industry in Malaysia has grown rapidly because of globalisation. Certain determinants have transformed the ecotourism environment and effortlessly improved its competitiveness. Prompt changes to the determinants of such changing environment are vital for keeping the leisure and tourism organisations competitive. Accordingly, for the ecotourism industry, understanding the determinants of tourists’ post-trip responses is essential. Given the significance of ecotourism competitiveness, service organisations should attempt to acquire resources and undertake efforts to increase the awareness of tourist behaviour and maintain their advantage. In response to the determinants of tourist behavioural intention, an interrelationship among marketing and socio-psychology constructs was included in this work. Hence, the core contribution of this study is a framework that empirically depicts marketing and socio-psychology concepts and their influence on tourist behavioural intention within the ecotourism industry. With regard to research aims, this study proposed a conceptual model encapsulating six constructs, namely, servicescape (SS), experience (EX), emotion (EM), perceived value (PV), satisfaction (SA) and behavioural intention (BI). The model entailed interconnected hypothetical relationships between the proposed constructs. This research further employed a quantitative research approach to assess the suggested conceptual framework. Multivariate statistical analysis was applied to ensure model robustness. Statistical techniques such as CFA and SEM were employed. CFA aimed to assist, refine and validate the measurement model by uncovering its robustness. By contrast, SEM assessed the conceptual framework by evaluating the relationships between constructs. For validation of mode, this research provided an empirical examination of the hypotheses. Firstly, the interrelationships between the constructs (1) SS–EX path, (2) EX–BI path and (3) SS–BI path were examined. Among the three hypotheses proposed, only the association between servicescape (SS) and experience (EX) was statistically proven. Secondly, this study further examined the mediation effect between constructs. Sufficient evidence proved that mediation effect occurred. The empirical findings in this study offered several implications. Firstly, this work added to the extant body of knowledge by expanding the studies of Chen and Chen (2010), Wang et al. (2012) and Brunner-Sperdin, Peter and Strobl (2012). Secondly, a service organisation should effectively manage its servicescape and the related components by taking care of the flora and fauna, upholding professionalism among service staff and maintaining the quality standards of diving equipment. Thirdly, in sustain ecotourism and its competitiveness, firms should pay attention and understand the elements of servicescape, experience, emotion, perceive value and satisfaction during the service consumption among tourists. This study contributes the finding that service organisations should construct and design services by considering the tourists’ service consumption experience and the corresponding values travellers obtain. Likewise, favourable responses are likely to be achieved by effectively facilitating the said determinants. Lastly, a refinement of policy practices should not be ignored. Such improvement further fosters the sustainability of the tourism industry through the enforcement of relevant rules and regulations. Policy implementation is crucial as regards encouraging ecotourism activities without jeopardising valuable natural resources through appropriate tourism practices. Hence, this study contributes to the body of knowledge by expanding prior research and extending the existing literature of marketing and sociopsychology within the ecotourism context. Significantly, the robustness of the theoretical model provides practical guidance for not just service organisations but also the tourism industry by maintaining competitiveness as a priority. In conclusion, the findings provide significant support for the proposed conceptual framework. Exploiting the market extensively by enhancing the servicescape and tourist experience is suggested. Thus, realising a positive intention must be in line with the activities of their independent dimensions, along with the support from organisations.